Ethnobotanical Uses, Nutritional Composition, Phytochemicals, Biological Activities, and Propagation of the Genus Brachystelma (Apocynaceae) - Adeyemi Oladapo Aremu; Nqobile P. Hlophe; Johannes Van Staden; Jeffrey F. Finnie (Horticulturae, 2022)
The Brachystelma genus (family: Apocynaceae) consists of geophytes that are traditionally utilised among rural communities, especially in East Africa, southern Africa, West Africa, and northern and western India. Apart from being used as a food source, they are indicated as treatment for ailments such as colds, chest pains, and wounds. This review provides a critical appraisal on the ethnobotanical uses, nutritional value, phytochemical profiles, and biological activities of Brachystelma species. In addition, we assessed the potential of micropropagation as a means of ensuring the sustainability of Brachystelma species. An inventory of 34 Brachystelma species was reported as a source of wild food and traditional medicine (e.g., respiratory-related conditions, pains, and inflammation) across 13 countries, predominantly in Africa and Asia. Brachystelma circinnatum and Brachystelma foetidum were the most popular plants based on the high number of citations. Limited data for the nutritional content was only available for Brachystelma edulis and Brachystelma naorojii, as well as phytochemical profiles (based on qualitative and quantitative techniques) for five Brachystelma species. Likewise, a few Brachystelma species have evidence of biological activities such as antimicrobial, antioxidant, and acetyl cholinesterase (AChE) inhibitory effects. Extensive studies on Brachystelma togoense have resulted in the isolation of four compounds with therapeutic potential for managing different health conditions. As a means of contributing to the sustainability of Brachystelma species, micropropagation protocols have been devised for Brachystelma glabrum, Brachystelma pygmaeum, Brachystelma ngomense, and Brachystelma pulchellum. Nevertheless, continuous optimisation is required to enhance the efficiency of the micropropagation protocols for these aforementioned Brachystelma species. Despite the large number of Brachystelma with anecdotal evidence as food and medicine, a significant number currently lack empirical data on their nutritional and phytochemical profiles, as well as their biological activities. The need for new propagation protocols to mitigate the declining wild populations and ensure their sustainability remains pertinent. This is important should the potential of Brachystelma species as novel food and medicinal products be achieved.